Research on the Visual Imagery of Posters Based on the Culture Code Theory of Design - Wen, Luo; Jingjing, Wang; Chen, Wang; Luyu, Sun (Frontiers in Psychology, 2022)
According to the Culture Code Theory of Design, posters can be divided into strategy aspect, meaning aspect, and technical aspect. This paper explored the impact of visual imagery on poster communication and effect focus on the meaning and technical aspects which directly related to the audiences. The visual imagery preference of ten public poster samples is collected from 40 participants by online questionnaire with the semantic differential method. The results show that the audience's visual imagery at the technical aspect is mainly related to the richness of colors, graphics, and texts. When receiving the information from the meaning aspect of the poster correctly, the visual imagery will be influenced by the type of theme. Most importantly, the same or similar visual imagery at the technical and meaning aspect encourages audiences to explore the deep information of posters. Poster works that keep visual imagery coherent and smooth at the two aspects can achieve a better effect.